The Clinical Particularities in Forming of Policystic Ovary Syndrome - J. J. Chebotareva (Медицинский вестник Юга России, 2011)
Purpose: Clinical particularities and conditions of the vegetative nervous system from the patients with forming polycystic ovary syndrome were studied.Materials and Methods: 364 patients aged 16-18 years old with forming polycystic ovary syndrome were examined. The control group included 364 practically healthy girls of the similar age with normal physical and sexual development. Methods of investigation included patient complaints and anamnestic data acquisition, clinical and gynecology survey, biological modeling of forming polycystic ovary syndrome.Results: It was determined that the patients with forming polycystic ovary syndrome had different breaches of vegetative and hormonal status and the exchange of catecholamine.Summary: Patients with forming polycystic ovary syndrome are in the high-risk group of the development of primary infertility, cardiovascular and oncologic pathology. They need carrying out timely dispensary actions directed on early diagnostics and timely treatment, including complex correction of the vegeto-hormonal status.